2004
DOI: 10.1213/01.ane.0000117282.72866.26
|View full text |Cite
|
Sign up to set email alerts
|

Change in Bispectral Index During Epileptiform Electrical Activity Under Sevoflurane Anesthesia in a Patient with Epilepsy

Abstract: During epileptiform electroencephalographic activity (EEG), the Bispectral Index shows an abnormal fluctuation caused by repeated abrupt alterations between normal EEG and abnormal epileptiform EEG patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 10 publications
3
40
1
2
Order By: Relevance
“…It is known that the BIS values are significantly affected when the EEG is abnormal. In patients with epilepsy abnormal BIS values have been reported due to increased d waves and h waves and the influence of epileptic activity [7][8][9]. In the two cases reported here the instability and differences in intra-operative BIS values between the left and the right were presumed to be due to these factors.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It is known that the BIS values are significantly affected when the EEG is abnormal. In patients with epilepsy abnormal BIS values have been reported due to increased d waves and h waves and the influence of epileptic activity [7][8][9]. In the two cases reported here the instability and differences in intra-operative BIS values between the left and the right were presumed to be due to these factors.…”
Section: Discussionmentioning
confidence: 59%
“…Sensors placed on the frontal region of head in these two cases were adequate for monitoring of spike activity. In addition, since changes in sevoflurane concentration [8] and hyperventilation during anaesthesia [17] alter the frequency of spikes, the anaesthetic effect on these can be assessed. Chinzei et al have previously reported that use of the EEG from the BIS monitor allowed detection of the disappearance of seizure activity during anaesthesia and intravenous anticonvulsant therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…A difference of 15 mmHg detected by non-invasive BP measurement identifies all patients with subclavian artery narrowing of greater than 50% [2]. Our patient had an inter-arm blood pressure difference of 30-35 mmHg, suggesting a subclavian artery stenosis of greater than 50% and blood pressure readings obtained from this arm would not represent true systemic blood pressure.…”
Section: ó 2006 the Association Of Anaesthetists Of Great Britain Andmentioning
confidence: 67%
“…As both the sympathetic and renin-angiotensin systems are blunted, the role of the vasopressin in restoring arterial pressure in these cases has been proposed [2]. Arginine-vasopressin, a postpituitary nine amino-acid peptide, stimulates vasopressin receptors -notably the vascular V1a receptors, to cause marked arterial constriction and has been used for septic and catecholamine resistant shock [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation